Pengaruh Video Persalinan Normal terhadap Kecemasan Ibu Hamil Menghadapi Persalinan di Wilayah Kerja Puskesmas Pangaribuan Kecamatan Pangaribuan Kabupaten Tapanuli Utara - Indah Dewi Sari; Sulastri Pakpahan (Universitas Batanghari Jambi, 2021)
Primigravida mothers in facing delivery would experience anxiety. Anxiety in pregnant women increases in the third trimester which can lead to complications for both the mother and the fetus. 80% of primigravida mothers experience anxiety just before delivery. Efforts that can be made to reduce anxiety can be by watching videos of normal childbirth. The aim of the study was to determine whether there was an effect of video of normal delivery on anxiety of pregnant women in facing childbirth in the Pangaribuan Health Centre, Pangaribuan District, North Tapanuli Regency in 2020.This study used a Quasi-Experimental Research type with the design used was One Group Pretest-Postest Design. The sample of this study were 10 pregnant women who were measured before and after the intervention watching normal childbirth videos. Based on the results the data analysis used univariate and bivariate analysis. Bivariate analysis using the Wilcoxon Rank Test, obtained a p value (Sig.2-tailed) of .006 <α: 0 .05, it can be concluded that there is an effect of Normal Delivery Videos on Anxiety of Pregnant Women Facing Childbirth in the Pangaribuan Health Centre, Pangaribuan District, District North Tapanuli 2020. These results conclude that there is a significant effect between normal delivery videos on the anxiety of pregnant women facing childbirth in the Pangaribuan Public Health Centre, Pangaribuan District, North Tapanuli . Suggestions for health care workers to provide more information to primigravida mothers about labor preparation to reduce feelings anxiety of pregnant women facing childbirth.